Modern technology of physical education of disabled students in conditions of inclusive education - S.G. Adyrkhaev (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
There is a problem of physical education of disabled students during period of their study in higher educational establishments. Insufficiency of this problem's studying conditioned fulfillment of research of perfection of physical education and sports system. Purpose: substantiation of physical education pedagogic technology for disabled students. Material: in experiment students with following nosologies participated: hearing, eyesight, muscular-skeletal apparatus, after effects of cerebral palsy, somatic diseases and diabetes. In total 664 students of 18-24 years' age took part in experiment. They were 337 boys and 307 girls. Results: we have worked out organizational-methodic algorithm, which permits to combine theoretical, scientific-methodic and practical training. Its basis is current information about students' psychic-physiological condition. We determined levels of health and physical condition, physical workability and physical fitness as well as psychic state of students. Demand in optimization of students' motor functioning during all period of study was substantiated as well as effective means of physical education and pulse regimes, considering peculiarities of nosologies. Students' orientation on sport style of life was formed. Conclusions: implementation of physical education pedagogic technology for students with different nosologies in the process of their studying stipulates solution of training, health-related and educational tasks. It is possible through creation of conditions for motor actions' training and intensification of motor functioning during all period of study. Practical application of the technology and received results points at integration of disabled students in students' medium.